Analysis of Early Surgical Treatment of Incorrectly Consolidated Gunshot Fractures of the Scapula - Telepenko, H.V.; Haiovych, V.V. (TERRA ORTHOPAEDICA, 2024)
Objective. The objective of our study was to analyze the structure of incorrectly consolidated gunshot fractures of the scapula and early outcomes of surgical treatment.Material and Methods. We analyzed 10 cases of incorrectly consolidated gunshot fractures of the scapula in Ukrainian Armed Forces servicemen, received as a result of combat operations, and early outcomes of surgical treatment. The main indications for surgical treatment were as follows: severe impairment of function of the upper limb due to pain, fractures of the articular surface of the scapula with displacement of fragments over 2 mm, fractures of the acromion with displacement of more than 8 mm, and damages to muscles and skin. In addition to radiography in standard projections, preoperative examination included computed tomography (CT). Evaluation of functional outcomes was carried out within 1 to 4 months according to the Oxford Shoulder Score (OSS) scale. The average period of postoperative survey was 2.6 months.Results. Incorrect consolidation of fractures was caused by a long period of preoperative preparation and conservative treatment of wounds in patients due to openness and infection of bullet wounds in 2 patients and shrapnel wounds because of mortar, artillery, tank and rocket attacks in 8 patients. Staged treatment until wound healing was carried out in hospitals and military hospitals of Ukraine using VAC (Vacuum-Assisted Closure) devices. Four cases were right-sided and six were left-sided; 7 of 10 cases were intra-articular fractures with displacement of fragments of the articular surface by 2 mm or more. The average duration of injury at the time of surgery was 4.2 months (range from 2 to 8 months). In addition to eliminating displacements and deformities of incorrectly consolidated fractures and osteosynthesis of fragments, the treatment included replacing the soft tissue defect of the shoulder and shoulder girdle with a non-free thoracodorsal musculocutaneous flap on a neurovascular pedicle in 3 of 10 patients. Seven patients had an isolated wound to the scapula area. Three of 10 patients had a combined wound to the scapula with a defect of the humeral head, upper third of the humerus, and acromial end of the clavicle. These patients underwent implantation of an articulating spacer, restoration of the configuration of the proximal end of the humerus, and reconstruction of the rotator muscles to make possible the shoulder joint arthroplasty. The average value according to the results of a survey of patients on the OSS scale was 20.2 (±4.39) points before surgery and 34.1 (±7.56) points after surgery, which can be considered a good result according to the OSS scoring system.Conclusions. The analysis of the early outcomes showed that reconstructive treatment of gunshot old fractures of the scapula creates biomechanical prerequisites for restoring the function of the upper limb, reduces pain syndrome, and allows for active postoperative rehabilitation.